ЕВГЕНИЈА ЈАНЧУЛЕВА ИЛИ ЗА ЕМАНЦИПАЦИЈАТА НА МАКЕДОНСКИТЕ ЖЕНИ ВО XIX ВЕК - Славчо Ковилоски (Институт за македонска литература, 2019)
Evgenija Janculeva, born Rakidzhieva (1875, Prilep - ?), was one of the most prominent Macedonian women in the 19th century, a teacher and activist for women's rights. She is the author of a comprehensive school report and of several short articles published in the newspapers of the time. She initiated an opening of a weekly school in which elderly illiterate women were taught. She participated in the Macedonian Revolutionary Movement and fought equally as her male counterparts. In her speeches she talked about the "emancipation of women" and demanded equal work conditions for women and men. With her activities, she became a role model for the future cultural and social struggles of the Macedonian women and served as an example of how to defend one’s ideals.
Keywords: Evgenija Janchuleva, Macedonian women, 19th century, the woman question, Prilep, emancipation of women